Sameness and repetition in contemporary media culture - Tosca, Susana (Emerald Publishing Limited, 2023)
The ebook edition of this title is Open Access and freely available to read online. Our culture has an uneasy relationship with repetition and sameness. On the one hand, we find familiarity pleasurable and soothing; on the other, we crave novelty and long for a sense of discovery. We blame algorithms, intent on selling us more of the same, and on a media industry too greedy to risk investing in intellectually challenging, radically new, products. Sameness and Repetition in Contemporary Media Culture takes a comprehensive approach that both theorises and historically grounds the idea of repetition in relation to media as something that is deeply embedded in our cultural tradition. This project received funding from the Carlsberg Foundation.